OVERVIEW OF SOCIO-CULTURAL ADAPTABILITY NEW STUDENTS IN SOUTH SUMATERA - Ulva, Maria; Rizandri, Dhavi; Fatrika, Fitria; Rahma, Rahma; Alrefi, Alrefi (Jurnal Kopendik, 2024)
This study aims to get an overview of the socio-cultural adaptability of new students in South Sumatra. This type of research is descriptive quantitative. There is a lot of research on the socio-cultural adaptability of new students, but for South Sumatra it is still very limited. The instrument used by the researcher was an adaptation questionnaire consisting of 37 items. The results showed that 149 students described in general social adaptation ability in the college environment: (5%) students have social adaptation ability is at a high level, (85%) students have social adaptation ability is at a moderate level, and (9%) students have social adaptation ability is at a low level. These results illustrate the importance of overseas students developing adaptability, this new thing can increase their knowledge to get to know the social and cultural environment.